In situ mass spectrometric and kinetic investigations of Soai's asymmetric autocatalysis - Trapp, Oliver; Lamour, Saskia; Maier, Frank; Siegle, Alexander F.; Zawatzky, Kerstin; Straub, Bernd Franz (Chemistry - a European journal, 2020)
Chemical reactions that lead to a spontaneous symmetry breaking or amplification of the enantiomeric excess are of fundamental interest in explaining the formation of a homochiral world. An outstanding example is Soai's asymmetric autocatalysis, in which small enantiomeric excesses of the added product alcohol are amplified in the reaction of diisopropylzinc and pyrimidine-5-carbaldehydes. The exact mechanism is still in dispute due to complex reaction equilibria and elusive intermediates. In situ high-resolution mass spectrometric measurements, detailed kinetic analyses and doping with in situ reacting reaction mixtures show the transient formation of hemiacetal complexes, which can establish an autocatalytic cycle. We propose a mechanism that explains the autocatalytic amplification involving these hemiacetal complexes. Comprehensive kinetic experiments and modelling of the hemiacetal formation and the Soai reaction allow the precise prediction of the reaction progress, the enantiomeric excess as well as the enantiomeric excess dependent time shift in the induction period. Experimental structural data give insights into the privileged properties of the pyrimidyl units and the formation of diastereomeric structures leading to an efficient amplification of even minimal enantiomeric excesses, respectively.
Gesehen am 09.09.2024